The Correlation Between Students’ Vocabulary Mastery and Their Reading Comprehension in Learning English of The Eleventh Grade Students of SMA N 11 Jambi - Desriani, Fitri; Suyadi, Suyadi; Aisyah, Siti (JELT: Journal of English Language Teaching, 2025)
One of the important abilities in learning English is reading. Reading comprehension is a fundamental skill in education, crucial for understanding and interpreting text across subjects. On this research, the researcher wants to find out whether there is correlation between students vocabulary mastery and their reading comprehension in  learning English, especially at SMA N 11 Jambi. This research investigates the relationship between vocabulary mastery and reading comprehension abilities among students at SMA 11 Jambi City. This research used Quantitative Method and using Pearson Correlation Coefficient as data analysis result. The population in this research is all of eleventh grade students at SMA N 11 Jambi City and took 35 students as sample on this research. The technique that used in this research to collect the data  was distributed the test about vocabulary and reading. From the research results, the researcher found that there was a correlation between the two variables and reached 0.892. According to the Pearson Correlation Coefficient guidelines, these results prove that the correlation between the two variables is a strong positive correlation. The conclusion that can be drawn from this study is that vocabulary has a very strong correlation with reading. Not only with reading, but with vocabulary, students can also master 3 other skills in learning English, namely speaking, listening, and writing.